DESIGN AND DEVELOPMENT OF COCONUT PALM (Cocos nucifera L.) ROOF SHINGLES - A.R. Floresca; F.R. Siriban; A.P. Gesmundo (International Coconut Community, 1989)
Tapered roof shingles from coconut wood were fabricated and treated separately with four preservatives, namely: copper‑chromearsenate, pentachlorophenol, copper sulfate and copper sulfate + potassium dichromate. Untreated and treated shingles were installed side in roof framed structures and exposed outdoor in the FPRDI